The utility of passive acoustic monitoring for using birds as indicators of sustainable agricultural management practices - Molina-Mora, Ingrid; Ruíz-Gutierrez, Viviana; Vega-Hidalgo, Álvaro; Sandoval, Luis (Frontiers in Bird Science, 2024)
Agriculture, which is spreading rapidly, is one of the major effectors on biodiversity – generally contributing to its decline. In the past few decades, most research efforts have focused on the impact of industrial agriculture on the environment and biodiversity. However, less attention has been paid on examining the impact of sustainable agricultural management practices on biodiversity. Challenges include the disruptive nature of some practices (e.g., agrochemical application) and the timing of others (e.g., tree pruning). Here, we highlight the value of passive acoustic monitoring in assessing the impact of agricultural management practices on biodiversity, using birds as indicators. We outline key considerations, including bird ecology and behavior, ARU sampling protocols, and data management. To demonstrate our approach, we present a case study from a coffee landscape in Costa Rica, where we analyzed the effects of pruning and pesticide application over two years. By focusing on selected focal species and using a subsample of the total hours recorded in combination with a mobile app for annotations, we found that pruning negatively impacted most species, while pesticide application adversely affected all species studied. Our methodology leverages technology to evaluate the impacts of agricultural management practices, offering insights to guide and assess sustainable agricultural strategies aimed at balancing biodiversity conservation with human well-being.